(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
Analysis of academic and methodological as well as specialized references (results if Internet sources monitoring) on the issues of technical training of highly-qualified weightlifters in various weight groups shows that the issue of improvement of athletes’ competition drills kinematics during educational and training process remains urgent nowadays. The aim of the article is to thoroughly analyze features of jerk kinematics of highly-qualified athletes (both genders) depending on the group of weight category in the process of competition activity. During the academic research, the following methods were used: analysis of academic and methodological references, Internet resources, pedagogical survey, competitions videos, biomechanical analysis of the barbell motion structure, methods of mathematical statistics. As a result of the research we have defined specifics of jerk kinematics of highly-qualified weightlifters depending on the weight groups. It has been proven that jerk kinematics of weightlifters (both genders) of various weight categories has its specifics: some jerk kinematics characteristics increase with the increase of weight and athletes’ weight categories; others remain unchanged. It has been found that jerk kinematics has differences in motion phase structure with weightlifters of various genders. The materials provided indicate existence of certain differences in the technique of competition drills execution by qualified weightlifters of various gender and weight categories according to kinematics of barbell motion in the second jerk move – from the chest. The obtained results prove the necessity to differentiate methods and means of improvement of technical mastery of qualified weightlifters (both genders) according to the weight categories taking into account barbell motion kinematics in certain phases.